Sejarah Psikologi Pendidikan Islam dan Dasar Psikologi Pendidikan Islam - Rokhimah, Siti; Saepudin, Ade; Rahadi, Rahmat (Lembaga Yasin AlSys, 2024)
Psychology as a science is currently influenced by Western scientific concepts. Islamic psychology examines the psychological phenomena of humans based on the sources of Islamic teachings, namely the Qur'an, Sunnah, and the thoughts of Muslim scholars and philosophers. This article discusses the history of Islamic educational psychology, which is divided into two periods, classical and modern, and explores the foundations of Islamic educational psychology. The classical period (7th to 13th century) features contributions from prominent figures such as Al-Kindi, Al-Farabi, Ibn Sina, Al-Ghazali, and Ibn Arabi. The modern period (19th century to present) includes significant contributions from figures like Muhammad Iqbal, Malik Badri, Abdul Hamid Abu Sulayman, and Syed Muhammad Naquib Al-Attas. The article also highlights the broad scope of Islamic psychology, covering various aspects of human life, and emphasizes its integration with modern scientific knowledge and Islamic values to address psychological issues.